A Geo-environmental Impact Assessment of Abattoir Effluent Discharge on Groundwater Quality in Igoba Area of Ondo State, Nigeria - Olumuyiwa Olusola Falowo; Moses Philip Otuaga (Indonesian Journal of Earth Sciences, 2022)
Assessment of groundwater resource around an abattoir site in Igoba area of Ondo State, southwestern Nigeria has been carried out, within 1.3 km radius from the abattoir site in order to determine the influence of the effluents discharge on quality of groundwater in the area, so as to forestall outbreak of diseases that can endanger human health. Eleven water samples were analyzed for physical, chemical and microbial parameters; and result subjected to spatial and statistical analysis using analysis of variance and Duncan’s multiple range of variance.  The obtained parameters mean ± SD are pH (5.5±0.50), turbidity (10±5.9 NTU), temperature (27.75±0.35 °C), conductivity (240±105.99µs/cm), total dissolved solid (158.9±46.8 mg/L), total hardness (92.1±14.2 mg/L), nitrate (7.3±4.3 mg/L), iron (0.24±0.04 mg/L), total alkalinity (14.57±4.87 mg/L), manganese (0.017±0.0079 mg/L), calcium (26.53±8.7 mg/L), magnesium (12.20±8.1 mg/L), chloride (21.86±7.39 mg/L), sodium (14.71±4.85 mg/L), bicarbonate (13.95±4.48 mg/L), nitrite (0.0336±0.0269 mg/L), dissolved oxygen (1.82±0.52 mg/L), chemical oxygen demand (133.1±53.7 mg/L), biological oxygen demand (29.55±10.93 mg/L), total coliform (9.36±6.05 cfu/100ml) and E.coli (0.5090±0.4700 cfu/100ml). The analysis of variance showed that statistically significant difference occurs among the parameters (p<0.05). All the measured parameters are within the standard limits of WHO and FEPA standards except pH, turbidity, BOD, and total coliform for samples collected within 610 m proximate distance from the site. This contamination is strongly aided by topography of the environment, as the discharged effluents/waste water flows westward and southwardly. Subsequently there is need for proper water treatment and environmental sanitation to prevent outbreak of epidemics and infections, while the government should enforce thorough regulations guiding establishment and operation of abattoir in the site if it can’t be relocated.